Numeracja i sposób oznaczania więźniów w obozie Stutthof - Chyrek, Agnieszka (Pamięć i Sprawiedliwość, 2006)
The article describes numeration and ways of identifying prisoners at the Stutthof camp in comparison with other concentration camps. The Stutthof camp operated since 2nd September 1939 till 9th May 1945 and belonged to the centrally organised system of concentration camps. It was a place of imprisonment for about 110 000 people, about 65 000 of whom became its victims.The way of numbering Stutthof concentration camp prisoners has not been a subject of a separate article yet. The method of labelling was settled on the basis of preserved camp documents: registry fi les, transport lists, personnel fi les, as well as accounts of people who survived at Stutthof.According to the available sources, in the Stutthof camp during all its existence there had been one series of numbers, which were given to the people staying both in the main camp and sub-camps. There was no double numeration and numbers of released or dead prisoners were not given to the new ones. People who were imprisoned for a second time were given another number. The documentation analysis allowed to estimate the number of prisoners shown in camp registry fi les in 1939–1945 and number of people put in Stutthof every month in 1939–1945.Registration of prisoners of Stutthof camp was done not only on the basis of numbers given to new prisoners, but also on the basis of special labels, which put prisoners into categories depending on the reason of imprisonment. The way of labelling with triangles of special colour had been worked out in Dachau camp and this scheme was used in other concentration camps, i.e. in Stutthof.The prisoner registration system was elaborate and bureaucratic. Prisoners were labelled as soon as they entered the camp, and labelling was accompanied with a „greeting ceremony” which was to show them where they had got into and what lot was awaiting them.